Effect of double growth factor release on cartilage tissue engineering. (14th November 2011) - Ertan, Ayşe Burcu; Yılgor, Pınar; Bayyurt, Banu; Çalıkoğlu, Ayşe Ceren; Kaspar, Çiğdem; Kök, Fatma Neşe; Kose, Gamze Torun; Hasirci, Vasif
Abstract The effects of double release of insulin‐like growth factor I (IGF‐I) and growth factor β1 (TGF–β1) from nanoparticles on the growth of bone marrow mesenchymal stem cells and their differentiation into cartilage cells were studied on PLGA scaffolds. The release was achieved by using nanoparticles of poly(lactic acid‐co‐glycolic acid) (PLGA) and poly(N‐isopropylacrylamide) (PNIPAM) carrying IGF‐I and TGF–β1, respectively. On tissue culture polystyrene (TCPS), TGF‐β1 released from PNIPAM nanoparticles was found to have a significant effect on proliferation, while IGF‐I encouraged differentiation, as shown by collagen type II deposition. The study was then conducted on macroporous (pore size 200–400 µm) PLGA scaffolds. It was observed that the combination of IGF‐I and TGF‐β1 yielded better results in terms of collagen type II and aggrecan expression than GF‐free and single GF‐containing applications. It thus appears that gradual release of a combination of growth factors from nanoparticles could make a significant contribution to the quality of the engineered cartilage tissue. Copyright © 2011 John Wiley & Sons, Ltd.